KONSEP IBN TAIMIYYAH TENTANG IBADAH DAN MU’AMALAH: TELAAH NORMATIF DAN HISTORIS SOSIOLOGIS - Mudhoffar, Mudhoffar (LPPI Universitas Al-Qolam Malang, 2017)
Ibn Taymiyyah is known as the inspiration of the Wahhabi movement that aims to the purification of the teachings of Islam. This movement departs from the separation between the ‘ub?diyyah and un-‘ub?diyyah teachings, which are also inspired by Ibn Taymiyyah's thought. In 'ib?dah, Ibn Taymiyyah holds the rule that as long as there is no ordered argument it should not be done. However, the notion of ib?dah according to Ibn Taymiyyah is not limited to mahdlah worship but more broadly. Whereas in mu'?malah, he holds the rule of allowing doing anything as long as there is no prohibition against it. In shaping the concept of 'ib?dah and mu'?malah, at first, Ibn Taymiyyah accepted it as something normative from the thought of Ahmad ibn Hanbal. But when he saw the social reality with the number of deviations' in ib?dah done by Muslims, the concept that has been obtained normatively from the thought of Ahmad ibn Hanbal is reaffirmed and expanded to become a sociological concept, in addition to being normative. Keywords: Ibn Taymiyyah, concept, ‘ib?dah, mu’?malah